Constructing a Pesantren halal hub model based on the Penta Helix framework for developing the halal economy in Indonesia - Rachman, Abdul; Ulpah, Mariya; Sangare, Bilaly (Indonesian Journal of Islamic Economics Research, 2026)
This study examines the construction of a Penta Helix-based Pesantren Halal Hub model as an innovation for halal economic development in Indonesia, given the substantial and growing number of Islamic boarding schools (Pesantren) nationwide and the significant expansion of the halal economy in recent years (SGIE 2024/2025). This potential is nonetheless underexploited, as Pesantren involvement in the halal industrial ecosystem remains limited by constraints in capital access, managerial skills, halal certification, and connectivity with global markets. Employing a descriptive qualitative method within the Penta Helix approach, the study finds that the model has substantial potential to strengthen Pesantren not only as centers of education but also as institutions for community-based halal economic empowerment. As an innovation in halal economic development, the model can increase the number of halal-certified Pesantrenproducts, expand market access through halal hubs and e-commerce platforms, strengthen collaborative networks among stakeholders, and support financing through productive waqf and ZISWAF. Realizing this potential requires collaboration among Pesantren, government institutions, industry, universities, communities, and Islamic social finance institutions. The study offers a reference for government bodies, halal industry actors, Pesantren, academics, media, communities, and Islamic social finance institutions in designing more integrated economic empowerment programs, ultimately strengthening the national halal industrial ecosystem and the economic independence of the Muslim community and Pesantren-surrounding communities.